Development and Validation of Liquid Chromatographic Method with DAD for the Quantification of Natamycin In Dairy Products - BİLĞİÇ ALKAYA, DİLEK (MARMARA UNIV, FAC PHARMACY, 2017)
In this paper high performance liquid chromatography method was developed for the determination of natamycin in dairy product in Turkish market. Chromatographic separation was achieved on a C8 column (150 mm x 4.6 mm x 5 mu m 100 mm) with a mobile phase of methanol : water : acetic acid (12:8:1 v/v/v), at 1ml/min flow rate with DAD detection at 303 nm. Natamycin was analysed simultaneously using HPLC-UV method of ISO 9233+2, 2007(IDF 140-2, 2007). The method was found linear over the concentration ranges of 0.01-0.8 mg/L. Correlation coefficients (r) of the regression equations were greater than 0.999. The LOD and LOQ values for UV and DAD were found 0.321 mg/kg and 0.355 mg/kg; 0.321 mg/kg and 0.388 mg/kg for cheese samples respectively. The relative recoveries obtained for the spiked cheese samples were between 90 and 110 %. Also the interday precision of the method was found as 1.874% and 3.442 % RSD values for UV and DAD dedections. From the results of the present study using HPLC-DAD indicated that it is not reasonable to attribute the determination of natamycin in cheese. Therefore, the difference of the validation parameters were found insignificant for both detections. However, It was succesfully applied to determination of 46 different cheese products and finding dealing with the presence of natamycin in cheese samples were presented.
Keywords: HPLC-DAD; validation; natamycin; antifungal agent; CHEESE